Do socially preferred firms disclose more ESG information? - Peng Z; Anderson HD; Chi J; Liao J (Emerald Publishing Limited, 2025)
Purpose While research shows “sin” firms voluntarily disclose more social responsibility information, little research examines such practices in socially preferred industries. This study aims to address this gap by contrasting firm-level environmental, social and governance (ESG) information disclosure of New Zealand firms. Design/methodology/approach This study extracts all New Zealand listed companies for which Bloomberg provides ESG data from 2010 to 2023. Besides, this study excludes firms in financial service sector. The final sample contains 52 companies and 514 firm-year observations. Findings This study find that retirement village firms and the healthcare industry whose operations are commonly considered to be socially preferred, disclose less ESG information than firms in other industries. This result remains after a series of robustness tests, including alternative measures and matching samples. The addition of ESG provisions in the 2017 New Zealand Exchange’s (NZX) Corporate Governance Code, female and independent directors have a significantly positive moderating effect on ESG disclosure. In addition, retirement village firms with higher financial constraints increase ESG disclosure. Furthermore, this study finds that increased ESG disclosure enhances market valuation and reduces the cost of debt. Research limitations/implications A natural limitation of this research is its limited sample size, focusing on New Zealand firms, which may limit the generalisability of the findings to other regions with different regulatory and cultural contexts. Practical implications This research suggests that firms in socially preferred industries, like healthcare and retirement villages, may need stronger incentives or guidelines to improve ESG disclosure. Enhancing corporate governance, particularly through independent and female directors, could positively influence ESG transparency, guiding policy and board composition strategies. Social implications The research highlights a potential gap in ESG disclosure among industries. This suggests a need for greater public awareness and advocacy to ensure that even socially favoured sectors are held accountable for their environmental and social impacts, promoting broader corporate responsibility. Originality/value This study contributes to the literature by revealing that socially preferred industries, such as healthcare and retirement villages, may disclose less ESG information than other sectors. It provides novel insights into the role of corporate governance, particularly the influence of female and independent directors, in enhancing ESG transparency.
Keywords: Corporate governance; Financial constraints; ESG disclosure; Socially preferred firms